Implementation of Social Forestry Policy: A Review of Community Access - Budi, Budi; Kartodihardjo, Hariadi; Nugroho, Bramasto; Mardiana, Rina (Forestry Faculty, Universitas Hasanuddin, 2021)
The issuance of social forestry licence and the achievement of benefits to the community in the post-licensing stage are still obstacles and difficulties for the community which is demanding the community access. The research aims to analyze the access of the community of social forestry licence holders in the pre-licence and post-licensing stages through field studies in forest community of Beringin Jaya Lampung and people’s forest plantation of Hajran Jambi qualitatively. In the pre-licence stage, the two license holder communities have the same access to all members who will be involved, information, facilitator, and government authorities. In the post-licensing stage, Beringin Jaya community has higher access to all members, facilitator, information, knowledge, government authorities, capital, technology, programs/activities of agencies and local markets, compared to Hajran community. Access to these matters is carried out by the community and facilitated by facilitator by linking the community to those who control these matters –which are not adequately provided by social forestry policies– through processes, mechanisms and social relationships. Successful facilitation of access requires networked capacity among community members and networking with other parties outside the community. The high level of access and networking capacity of community to obtain benefits from the implementation of social forestry policies must be supported by the suitability of subject-objects in granting licence at the pre-licence stage and the availability of supporting infrastructure.